Nickel‐Catalyzed Arylboration of Alkenylarenes: Synthesis of Boron‐Substituted Quaternary Carbons and Regiodivergent Reactions. Issue 32 (28th June 2019) - Chen, Liang‐An; Lear, Alan R.; Gao, Pin; Brown, M. Kevin
Abstract: A method for the construction of boron‐substituted quaternary carbons or diarylquaternary carbons by arylboration of highly substituted alkenylarenes is presented. A wide range of alkenes and arylbromides can participate in this reaction thus allowing for a diverse assortment of products to be prepared. In addition, a solvent dependent regiodivergent arylboration of 1, 2‐disubstituted alkenylarenes is presented, thus greatly increasing the scope of products that can be accessed. Abstract : Boron‐substituted quaternary carbon or diarylquaternary carbon centers are constructed by arylboration of highly substituted alkenylarenes. A wide range of alkenes and arylbromides can participate in this reaction. In addition, a solvent dependent regiodivergent arylboration of 1, 2‐disubstituted alkenylarenes is presented, thus greatly increasing the scope of products that can be accessed.